The lighthouse work of Sir James Chance baronet - Chance, James Frederick, 1856-1938 (Smith, Elder, 1902)
This title deals with the work of James Timmins Chance in bringing his high mathematical skills to the optical side of lighthouse construction, sometimes in collaboration with the greatest engineers in this field.